PERFORMANCE OF GROWING AND FINISHING PIGS FED CUSO4 TREATED MOC (Indian Journal of Animal Production and Management, 2013)
An experiment was conducted to investigate the effect of feeding CuSO4 treated MOC diet on the performance and nutrient utilization of growing and finishing pigs. Eighteen weaned crossbred (Hampshire X Assam local) piglets were distributed three groups having six piglets each in a completely randomized design. The experimental rations were prepared for growing (2-5 months) and finishing (5-8 months) pig containing no MOC (T1), 10% MOC (T2) and 10% treated MOC (T3) and piglets were offered twice daily. No significant (P>0.05) effect on weight gain influenced by either untreated or treated MOC with CuSO4. However, higher weight gain, better feed efficiency was observed in CuSO4 treated group but no significant (P>0.05) differences was achieved in the carcass characteristics of pigs fed different diets.
Keywords: CUSO4, glucosinolate; MOC; crossbred piglets